2008
DOI: 10.1021/jf8013074
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of Flavonoids in the Cellular Antioxidant Activity Assay

Abstract: Chemical antioxidant activity assays are used extensively to evaluate the potential bioactivity of plant foods and their phytochemical constituents, but they do not mimic the complexity of biological systems. The cellular antioxidant activity (CAA) activity assay was developed to be a more biologically relevant model to measure antioxidant activity. Structure-activity relationships of flavonoids have been determined in many chemistry antioxidant activity assays, and they vary with the protocols. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
223
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(242 citation statements)
references
References 46 publications
(87 reference statements)
15
223
0
4
Order By: Relevance
“…However, it is not excluded that the position of OH groups in phenolic compounds could possibly influence the chemical properties of the molecules. Such an effect would be due to OH groups in the ortho-position of the B ring as well as those associated with a 2,3-double bond combined with a 4-keto group in the C-ring, as they are known to be important structural determinants for the anti-oxidant activity of flavonols (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not excluded that the position of OH groups in phenolic compounds could possibly influence the chemical properties of the molecules. Such an effect would be due to OH groups in the ortho-position of the B ring as well as those associated with a 2,3-double bond combined with a 4-keto group in the C-ring, as they are known to be important structural determinants for the anti-oxidant activity of flavonols (14).…”
Section: Discussionmentioning
confidence: 99%
“…Surprising again, initial DPPH radical scavenging activity was highest in the basic paste even low in total phenolic content. This result confirmed that antioxidant activity may not well relate to total phenolic content [28]. DPPH radical scavenging activity of the garcinia paste without added salt kept in both storage temperatures increased in the first 2 mo before decreased and was lowest at end of storage.…”
Section: Dpph • Free Radical Scavenging Dpphmentioning
confidence: 51%
“…This may be a good explanation of using many assays to evaluate antioxidant activity [29]. However, some researchers mentioned that in vitro antioxidant activity such as DPPH, FRAP, ABTS and metal chelation activity may not responsible for antioxidant activity in vivo or even food system therefore using cellular antioxidant activity assay was more useful and close to body system [28,30].…”
Section: Ferric Reducing/antioxidant Power (Frap)mentioning
confidence: 99%
“…Currently, there are papers published on the in vitro antioxidant activity of flavonoids and a correlation between the antioxidant capacity and chemical structure (Wolfe and Liu, 2008). Ahn et al (2009) found that the anti-angiogenic action of various components of propolis, such as caffeic acid phenyl ester, kaempferol, and quercetin, is correlated with antioxidant capacity of the same (Ahn, et al, 2009).…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%